Fly ash as a substitute for cement and polypropylene fibers in concrete mix design - Farfán Córdova, Marlon Gastón; Ramírez Alayo, Ederlin; Rubio Reyes, Marcos Josué (LACCEI, 2025)
The research focused on analyzing the effect of fly ash (FA) and polypropylene fibers (PPF) on the mechanical properties of concrete with a compressive strength of f’c = 280 kg/cm². The objective was to determine the influence of adding FA and PPF on the mechanical properties of the concrete. Concretes with FA in proportions of 5%, 10%, and 15%, and PPF in amounts of 350 g/m³, 480 g/m³, and 530 g/m³ were analyzed, evaluating their compressive strength (CS) at 7, 14, and 28 days, and their indirect tensile strength (ITS) at 28 days. Regarding CS, the results showed that at 7 days, the concrete without additives reached 128.05 kg/cm², while with 10% FA and 480 g/m³ of PPF, the strength increased to 256.81 kg/cm². At 14 days, the concrete without additives achieved 155.80 kg/cm², improving to 280.88 kg/cm² with the additives. At 28 days, the concrete without additives reached 281.68 kg/cm², while with 10% FA and 480 g/m³ of PPF, the strength increased to 383.75 kg/cm². Regarding ITS, it was observed that with 10% FA and 480 g/m³ of PPF, the highest strength was obtained, with 49.57 kg/cm². In conclusion, the appropriate proportion of additives to improve the mechanical properties of the concrete is 10% FA and 480 g/m³ of PPF.